Transcriptome and gene expression analysis of Rhynchophorus ferrugineus (Coleoptera: Curculionidae) during developmental stages - Hongjun Yang; Danping Xu; Zhihang Zhuo; Jiameng Hu; Baoqian Lu (PeerJ, 2020)
Background Red palm weevil, Rhynchophorus ferrugineus Olivier, is one of the most destructive pests harming palm trees. However, genomic resources for R. ferrugineus are still lacking, limiting the ability to discover molecular and genetic means of pest control. Methods In this study, PacBio Iso-Seq and Illumina RNA-seq were used to generate transcriptome from three developmental stages of R. ferrugineus (pupa, 7th-instar larva, adult) to increase the understanding of the life cycle and molecular characteristics of the pest. Results Sequencing generated 625,983,256 clean reads, from which 63,801 full-length transcripts were assembled with N50 of 3,547 bp. Expression analyses revealed 8,583 differentially expressed genes (DEGs). Moreover, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that these DEGs were mainly related to the peroxisome pathway which associated with metabolic pathways, material transportation and organ tissue formation. In summary, this work provides a valuable basis for further research on the growth and development, gene expression and gene prediction, and pest control of R. ferrugineus.